2018
DOI: 10.1029/2018jb015888
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Submarine Volcanic Activity at Monowai: Constraints From Long‐Range Hydroacoustic Measurements

Abstract: Monowai is a submarine volcanic center in the Kermadec Arc, Southwest Pacific Ocean. In the past, activity at the volcano had been intermittently observed in the form of fallout at the sea surface, discolored water, changes in seafloor topography, and T phase seismicity, but there is no continuous record for more recent years. In this study, we investigated 3.5 years of recordings at a hydrophone array of the International Monitoring System, located near Juan Fernández Islands, for long‐range underwater sound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…However, the direct relation between the bathymetric slope and its spatial extent and the incidence angle of the signals is unclear. Metz et al (2018) indicated a systematic counterclockwise deviation of 0.4 • for the observed signal of the Monowai Seamount compared to the true geodesic angle of arrival. This deviation could partially be attributed to the indirect effect of the steep slope near H03S as indicated by array processing and cross-correlations.…”
Section: Discussionmentioning
confidence: 92%
“…However, the direct relation between the bathymetric slope and its spatial extent and the incidence angle of the signals is unclear. Metz et al (2018) indicated a systematic counterclockwise deviation of 0.4 • for the observed signal of the Monowai Seamount compared to the true geodesic angle of arrival. This deviation could partially be attributed to the indirect effect of the steep slope near H03S as indicated by array processing and cross-correlations.…”
Section: Discussionmentioning
confidence: 92%
“…Given a stationary and comparable source, the phase-velocity dispersion curve could be retrieved similar to Kästle et al (2016). Despite the clear modal signature in Figure 2b, the MVC is not a perfect stationary source with an identical signature for each event (e.g., Metz et al, 2018).…”
Section: Example Ccfmentioning
confidence: 97%
“…(2016). Despite the clear modal signature in Figure 2b, the MVC is not a perfect stationary source with an identical signature for each event (e.g., Metz et al., 2018).…”
Section: Cross‐correlation Functionsmentioning
confidence: 99%
See 2 more Smart Citations